Familiarization Trip Strategy to introduce Jakarta Textile Museum to Foreign Tourist - Latisha Anintya; M. Megasuryo Firdaus; Sylvia Desianty (Technium Social Sciences Journal, 2020)
This research is conducted to analyze how the Familiarization Trip strategy is done, the result, and the obstacle. Themethodusedin this research is descriptive qualitative using the Nine Steps of Public Relations by Ronald D. Smith to analysis the strategy, interview and data research to analysis the result and the obstacle. The result of this research explains that Familiarization Trip has been done well but in the other hand has not given significant result to the increasing number of foreign tourists visiting Jakarta Textile Museum.